(untitled) (Jurnal EurekaMatika, 2022)
ABSTRACT The lowest rock layer can indicate the earliest period, while the top rock layer can suggest the most recent era. Backcasting, or the prediction of past rock strata, is crucial because it can make drilling operations more cost-, time-, and labor-effective. The objective of this research is to investigate the Space-time Autoregressive Integrated Moving Average (STARIMA) model and apply the STARIMA (1,1,1) model to predict and identify the rock strata. The research process begins with calculating the location weights and parameter estimates. Furthermore, the STARIMA (1,1,1) modeling was carried out on the in-sample data with the parameter estimates that have been obtained. Then the residuals in the model were tested to see the assumptions obtained. After that, predictions were made to obtain the gamma-ray log value for the previous 5 depths. The study’s findings indicate that there is a large with the RMSE measuring average values of 21.15 and 32.87, respectively. The smallest gamma ray log value obtained from the prediction results from a depth of 96 m to 96.8 m is 11.5666 API and the largest is 26.1699 API. Overall, the results of the prediction indicate that the rock layers contain coal. ABSTRAK Lapisan batuan terendah dapat menyatakan waktu tertua dan lapisan batuan tertinggi dapat menyatakan waktu yang lebih muda. Prediksi terhadap lapisan batuan lebih tua (backcasting) menjadi penting karena dapat membantu kegiatan pemboran agar efektif dan efisien dalam waktu, tenaga dan biaya. Tujuan dari penelitian ini adalah mengkaji model Space-time Autoregressive Integrated Moving Average (STARIMA) dan mengaplikasikan model STARIMA(1,1,1) pada data log sinar gamma untuk memprediksi dan mengidentifikasi lapisan batuan. Proses penelitian ini diawali dengan menghitung bobot lokasi dan estimasi parameter. Selanjutnya dilakukan pemodelan STARIMA(1,1,1) pada data in-sample dengan estimasi parameter yang telah diperoleh. Kemudian residual pada model tersebut diuji untuk melihat asumsi yang didapat. Setelah itu, prediksi dilakukan untuk memperoleh nilai log sinar gamma untuk 5 kedalaman sebelumnya. Hasil dari penelitian ini adalah data in-sample dan out-sample menunjukkan terdapat galat yang cukup besar dengan nilai ukur RMSE sebesar 21,15 dan 32,87. Diperoleh nilai log sinar gamma terkecil pada hasil prediksi dari kedalaman 96 m hingga 96,8 m adalah 10,3460 API dan terbesar adalah 26,1699 API. Secara keseluruhan, hasil prediksi menunjukkan terdapat kandungan batubara pada lapisan batuannya.